In Vitro Antimicrobial Activity of Essential Oils from Sardinian Flora against Cutibacterium (Formerly Propionibacterium) acnes and Its Enhancement by Chitosan - Claudia Juliano; Mauro Marchetti; Maria Luisa Pisu; Marianna Usai (MDPI AG, 2018)
The in vitro antibacterial activity of some essential oils from Sardinian flora, both alone and in combination with chitosan, was investigated against a strain of Cutibacterium acnes, a bacterium involved in pathogenesis of acne. The composition of the essential oils was determined by gas chromatography and gas chromatography/mass spectrometry. The results of this investigation demonstrated that some of the oils examined, characterised by different chemical profiles, possessed some activity against C. acnes. Interestingly, this antibacterial effect was enhanced by sub-inhibitory concentrations of chitosan. These observations suggest the potential application of this synergy in the development of innovative topical formulations useful in the management of acne.